STABILITAS KARAKTER MORFOLOGI 10 AKSESI CABE JAWA (Piper retrofractum Vahl.) DI KEBUN PERCOBAAN CIKAMPEK - Wawan Haryudin; Otih Rostiana (Buletin Penelitian Tanaman Rempah dan Obat, 2011)
Stability of 10 Accessions of Java Long Pepper (Piper retrofractum Vahl.) Based on Their Morphological Characteristics at Cikampek Research StationJava long pepper (Piper retrofractum) is an Indonesian native medicinal plant, grows in the yard, field or any humid lands. Valuable parts of java long pepper used as medicine are fruit, leaves and roots. Fruits of java long pepper contains piperin, chavicine, palmatix acid, tetrahy-dropiperic acid, 1-undecylenyl-3, 4-me-thylledioxy benzene, piperidine, essential oil, N-isobutyldeka-trans-4-dienamide, and sesamine. An experiment was perfor-med in Cikampek Research Station (50 m above sea level, C climate type in the classification Schmidth and Ferguson). This experiment was conducted since Ja-nuary to December 2005. Direct observa-tion of some accessions was made to germplasm of java long peppers collected from production center areas in 2003. The aim of this study is to identify mor-phological stability of 10 accessions of java long pepper collection. Parameters observed were stem, leaves and fruit cha-racteristics. Results showed that 10 ac-cessions of java long pepper tested were adapted well at new agro-ecological areas based on stability of morphological charac-ter of leaf, stem and fruits. Except, shape of leaf have changed from lancet to oval. Further, cluster analysis showed that 10 accesions of java long pepper were clas-sified into 2 clusters. The first cluster was divided  into 2 sub clusters on which the first sub cluster consists of 6 accessions and the second one consists of 2 acces-sions as classified by length of shortest stem node (3.69-4.05 cm). The second cluster, there were 2 accessions which were separated from one to the others based on the smallest leaves width (2.11-3.48 cm).